2008
DOI: 10.2174/138920008786049276
|View full text |Cite
|
Sign up to set email alerts
|

Grapefruit Juice-Drug Interaction Studies as a Method to Assess the Extent of Intestinal Availability: Utility and Limitations

Abstract: This study aims to assess utility and limitations of grapefruit juice (GFJ) interaction studies as alternative in vivo approach to estimate intestinal availability (F(G)) in comparison to the predominantly used i.v./oral method. The F(G) estimates were obtained from the ratio of AUC in the control and the GFJ group reported previously. Due to large variability in the study design, the following inclusion criteria were applied for the selection of clinical studies: no change in elimination half-life in the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
76
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 122 publications
3
76
0
Order By: Relevance
“…Furthermore, for both drugs CL h approaches Q h , which impedes accurate estimation of in vivo F G , bearing in mind that this parameter is indirectly assessed from intravenous/oral data. Indeed, whereas intravenous/oral data for atorvastatin suggested an F G value of 0.24, grapefruit juice (GFJ) interaction data suggested a less extensive intestinal contribution to atorvastatin first-pass metabolism: F G, GFJ ϭ 0.56 (Gertz et al, 2008a). In the case of tacrolimus, F G predictions were highly variable among the different microsomal pools used within this study, showing a general overprediction trend.…”
Section: Prediction Of Human Intestinal First-pass Metabolismmentioning
confidence: 67%
See 3 more Smart Citations
“…Furthermore, for both drugs CL h approaches Q h , which impedes accurate estimation of in vivo F G , bearing in mind that this parameter is indirectly assessed from intravenous/oral data. Indeed, whereas intravenous/oral data for atorvastatin suggested an F G value of 0.24, grapefruit juice (GFJ) interaction data suggested a less extensive intestinal contribution to atorvastatin first-pass metabolism: F G, GFJ ϭ 0.56 (Gertz et al, 2008a). In the case of tacrolimus, F G predictions were highly variable among the different microsomal pools used within this study, showing a general overprediction trend.…”
Section: Prediction Of Human Intestinal First-pass Metabolismmentioning
confidence: 67%
“…3 (Yang et al, 2007). F G predictions from the Q Gut model were compared with in vivo F G estimates obtained either from intravenous/oral or grapefruit interaction data (Galetin et al, 2008;Gertz et al, 2008a) and are summarized in Table 5. For indinavir, the F G value was estimated from intravenous/oral data reported by Yeh et al (1999).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Early studies in liver transplant patients during the anhepatic phase indicated the relative importance of the gut extraction to the first-pass metabolism for drugs such as midazolam and cyclosporine (Paine et al 1996). Further clinical evidences were obtained in the grapefruit juice interaction studies, where coadministration of grape-fruit juice result in the inhibition of gut CYP3A4 without significantly affecting the hepatic metabolism of drugs like felodipine (Gertz et al 2008). However, assessment of the quantitative contribution of intestinal and hepatic extraction in first-pass metabolism is limited by ethical and technical challenges.…”
Section: Intestinal Metabolismmentioning
confidence: 99%